Hubungan Kebugaran Jasmani dengan Kemampuan Renang Gaya Bebas 50 Meter pada Atlet Renang Tirta Intan Swimming School Silampari Kota Lubuklinggau - Lutviansyah, Muhamad; Suhdy, Muhammad; Supriyadi, Muhammad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Swimming which is currently in demand by the age group has transformed into an achievement sport that is often contested both at the regional level to the national level. So it takes athletes who have good abilities such as for example in terms of physical fitness. This study aims to determine how the relationship between physical fitness and the ability to swim 50-meter freestyle in swimming athletes of Tirta Intan Swimming School Silampari Lubuklinggau City. This research includes quantitative research which focuses more on data and numbers to get research results. The research method used is correlation (relationship) which will be investigated more deeply related to the relationship between physical fitness and the ability to swim 50 meters freestyle in athletes at Tirta Intan Swimming School Silampari Lubuklinggau City. The population consisted of 32 swimming athletes and 16 athletes were taken as samples using purposive sampling techniques. The data collection technique used physical fitness tests on the archipelago guidelines and a 50-meter freestyle swimming test. As for the data analysis techniques, namely normality tests, linearity tests and hypothesis tests using SPSS version 25. Based on the significant value of Sig. (2-tailed): It is known that the value of Sig (2-tailed) between emotional intelligence (X) and shooting skill (Y) is 0.29. Based on the results of data analysis, testing the results of the study, it can be concluded that: There is a significant relationship between physical fitness and freestyle swimming ability in Tirtan Intan Swimming School Silampari Athletes Lubuklinggau City. The correlation efficiency obtained r calculate = 0.544 > r table = 0.497 so Ho is accepted. Furthermore, the contribution of physical fitness affects the ability to swim freestyle with a contribution of 29.6%. Keywords: KU IV’s Athlete, Physical Fitness, Freestyle swimming